HUBUNGAN KEKUATAN OTOT TUNGKAI DENGAN KETEPATAN TENDANGAN DALAM PERMAINAN SEPAKBOLA MAHASISWA KEPELATIHAN OLAHRAGA SEMESTER 3B UNIVERSITAS RIAU - Chandra, Novrizal; ', Slamet; ', Saripin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract :Based on examination of semester students 3B Coaching Sport that the shooting of students who follow college football is still not good, it is known that the student's knowledge of the basic techniques of football is still relatively low and the physical condition of the poor also affect the shooting, but the basic technique and physical condition is a technique that must be mastered by a soccer player. The purpose of this research is to know about the relationship between leg muscle strength with a precision shot towards the goal in the game sepkbola Semester 3B Riau University. In this study constitutes the entire pupulasi numbering 34 people (Arikunto, 2006: 134), where the population is less than 100 then it is better taken all. Then the samples used in this study is 34 people. The instrument used to collect the data in the study is to test the leg with a leg muscle strength dynamometer and precision kicking the ball toward the goal. The data obtained in the analysis using product moment correlation.Keywords: Muscle Limb, Kick, Football